Evaluation of Near-net-zero-energy Building Strategies: A Case Study on Residential Buildings in Jordan - Ali, Hikmat H.; Abu Al-Rub, Fahmi A.; Shboul, Bashar; Al Moumani, Hind (International Journal of Energy Economics and Policy, 2020)
Residential buildings contribute a significant share of energy consumption in Jordan, consuming 23% of total energy demand. It is the highest electrical energy consuming sector in Jordan, where it accounted for approximately 43% of the total electricity consumption in the year 2016. Therefore, improving the energy performance of existing residential buildings in Jordan is likely to reduce energy usage (approach net zero energy) and would be a means to minimizing national electrical consumption. A typical house model located in Irbid is selected as a case study for the near zero energy design and saving energy objective. The study investigates the economic and computational potential of various integrated passive and active design systems for the Jordanian residential building sector, by focusing on several parameters including orientation, layout, type of insulation, type of windows, shading system, type of ventilation system which used a comprehensive and detailed model of the Natural Convection Air-Cooled Condenser integrated to stack (NCACC) as new efficient ventilation method, and using of two renewable energy technologies; PV and flat plate solar thermal collector during the design of the buildings. This study uses three-strategies of building energy analysis in order to achieve near Net Zero Energy Building (nNZEB) in Irbid, Jordan. Two approaches (computational and analytical) could be utilized for the identification of energy building performance analysis. A dynamic building energy modeling and simulation software with different climatic conditions was utilized to identify the best building energy model. A suitable economic evaluation criterion was used to estimate the payback period of all systems applied. Keywords: near-net-zero-energy building, Residential Buildings, Energy Usage, Design Strategies JEL Classification: Q2 DOI: https://doi.org/10.32479/ijeep.10107